Managing YouTube Channel as a Virtual Da'wah Movement for Islamic Moderatism - M Hadi Purnomo (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2021)
This paper aims to explain the managing of virtual da'wah carried out by the Sabilut Taqwa Santri Youth Association (IRRSAT) in Jember, East Java. Digital da'wah initiated by IRSSAT is an effective solution for Muslims during the current pandemic. The method of data collection in this study was conducted by interview and observation. The results of this study indicate that the virtual da'wah management carried out by the IRSSAT community not only educates the Islamic community with ritual worship tutorials but also carries a mission to spread social and tolerant Islamic teachings. By carrying out the teachings of Ahlussunnah wal Jamaah Annahdliyah, IRSSAT makes straightforward da'wah content according to the religious needs of today's society by being packaged creatively and attractively. Using YouTube, the IRSSAT Official Channel has produced 285 videos with 35,541,321 views and 446,000 subscribers through a digital platform. IRSSAT uses the income obtained from YouTube for religious, social activities such as mass circumcision, donations to orphans, and other activities. The management of virtual da'wah carried out by IRSSAT can be a reference in the management of mosques in Indonesia to spread Islamic teachings that are polite and tolerant.